ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO PROFITABILITAS DAN METODE ECONOMIC VALUE ADDED (EVA) PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2010-2013 - PERIANSYA PERIANSYA (EKSISTANSI, 2014)
Datas that writer got are financial statements on 2010, 2011, 2012 and 2013, company overview, and the company’s organizational structure. The kinds of analysis are analysis of profitability ratio, analysis of WACC calculation, and analysis of EVA calculation. After writer did analysis of calculation so it can be concluded that the company has profitability ratio that fluctuating per year. While for the calculation of EVA in 2010, 2012 and 2013 considered good because EVA>0 but in 2013 the condition of the financial performance of PT Indofood Sukses Makmur Tbk rated unfavorable because EVA<0. From the conclusion of analysis above. the company should be maintain and improve the financial performance every year especially on the financial performance in order to maximize the rate of return on capital in the future.